THE EMPIRICAL STUDY OF PSYCHOSEMANTICS OF CHILDREN’S DRAWING: WALDORF EXPERIMENT - Borodulkina, Tetiana Oleksandrivna (Insight: the psychological dimensions of society, 2019)
The results of the psychosemantic analysis of the children’s drawings are represented in the article. We compared the drawings of schoolchildren from two types of classes – the Waldorf classes and the general education classes of the All-Ukrainian experimental educational institution – Zaporizhzhia secondary school № 66. According to the Order of the Ministry of Education and Science of Ukraine dated December 24, 2014, No. 1509 in this school an experiment entitled «Provision of children’s mental health by means of the Waldorf pedagogy» was opened. In our longitudinal study we rely on the assumption that the pedagogical system influences the mental development of a child; the results of such an impact can be investigated using the analysis of children’s drawings, relying not only on generally accepted formal indicators, but also on drawing’s psychosemantic indicators (content, context). The study of psychosemantic peculiarities of children’s drawings drawn by schoolchildren of secondary school №66 was performed by us during three years. The data analyzed in this study was obtained from 116 to 165 schoolchildren (the parallel of the first, second, third, fourth and fifth years). The pupils have made 5070 drawings in the process of performing F.Williams’s Test of Creativity and Divergent Thinking (modified by E.Tunik) and Children’s human figure drawings Test. Waldorf pupils produced larger and more scene-based drawings; drawings with more signs of movement. As for the drawings of children from general education classes, they are characterized with the image of abstract drawings, individual objects without any background (context), the lack of a storyline and signs of movement. Such features of the drawings reflect the fact that students of Waldorf classes more often experience the world and themselves in integrity, unity, in a certain context and in vivid interaction with it; whereas students of general education classes perceive the world not through the experience of unity with it, but through the perception of its individual components; perceive themselves in this world as something separate.